Band alignment at a MgO/GaSb heterointerface using x-ray photoelectron spectroscopy measurements. (6th July 2016) - Li, Ruxue; Wei, Zhipeng; Liu, Xue; Li, Yongfeng; Fang, Xuan; Tang, Jilong; Fang, Dan; Gao, Xian; Wang, Dengkui; Hao, Yongqin; Yao, Bin; Ma, Xiaohui; et al.
Abstract: The valence band offset (Δ E V ) of a MgO/GaSb heterostructure was determined using x-ray photoelectron spectroscopy measurements. A Δ E V value of 2.84 ± 0.10 eV was calculated by using Ga 3d3/2 and Mg 2p1/2 binding energies as references. Taking the empirical band gaps of 7.83 eV and 0.73 eV for MgO and GaSb thin films into consideration, respectively, we obtained the type-I band alignment of a MgO/GaSb heterostructure with a conduction band offset (Δ E c ) of 4.26 ± 0.10 eV, suggesting a nested interface band alignment.